“Estudio comparativo en la elaboracion de biofilm a partir de almidon de maiz (Zea Mays) y proteina de leche con adicion de glicerina como agente plastificante, obtenida durante el proceso de biodiesel en la estacion de E.E.A. El porvenir – Distrito de Juan Guerra - Moreno García, Alan Jymm (2013)
The aim of the work was to evaluate the effect of the addition of glycerin in diverse concentrations (15 %, 25 %, 35 %) in the physical and mechanical properties of formulation of movies (biofilms) of starch of maize and caseinato of sodium. The variables of response evaluated were: thickness, color, solubility and force of break. The elaborated formulations went for the method of molded and dried to the environment to a temperature of 25 º C. They are prepared by 100 mi. of water and the addition of different proportions of starch of maize and caseinato of sodium by glycerin by concentrations of: 15 %, 25 %, 35 % p/p. lt was used by the purpose of improving the physical and mechanical characteristics since it allows us to obtain more uniform structures, for his use in the industry. With what it concerns to the. physical tests were observed that similar the glycerin is increased there is an increase in the thickness which there decided with a micrometer model DDR-6000 Suhl, concluding that the formulation of starch of maize more glycerin 1 turn out to be more uniform in thickness, with the determination of the color measured up to a digital Colorimeter CR - 400 And was observed that the most out-standing formulation was that of starch of maize more glycerin to a concentration of 15 % and in caseinato of sodium more glycerin to a concentration 25 % turning out to be the best formulation that of starch of maize more glycerin. With the force of break the movies by means of a test of puncture using a te: xturómetro 1 shape Stentar 11 11009 STR, one determined that similar the concentration of glycerin is diminished it increases the force of break up to a maximum point between 7.93Nfor15 % Of glycerin more starch and 9.61 N for 35 % of glycerin with caseinato of sodium concluding that as for the formulation of caseinato of sodium more glycerin is the best for being more resistant. 11 The solubility in water evaluated the dissolution of the biofilms, was observed that the formulation of starch more glycerin is that better resistance offered in all the concentrations. On the basis of the realized tests and the variables evaluated as thickness, color, force of break, water solubility can conclude that better physical and mechanical property of formulation of biofilms is that of starch of maize more glycerin, with what it is possible to conclude that the movie assembles the best characteristics.